Acetylcholine induces GABA release onto rod bipolar cells through heteromeric nicotinic receptors expressed in A17 amacrine cells - Elgueta, Claudio; Vielma, Alex H.; Palacios, Adrian G.; Schmachtenberg, Oliver (Frontiers in Cellular Neuroscience, 2015)
Abstract Acetylcholine (ACh) is a major retinal neurotransmitter that modulates visual processing through a large repertoire of cholinergic receptors expressed on different retinal cell types. ACh is released from starburst amacrine cells under scotopic conditions, but its effects on cells of the rod pathway have not been investigated. Using whole-cell patch clamp recordings in slices of rat retina, we found that ACh application triggers GABA release onto rod bipolar (RB) cells. GABA was released from A17 amacrine cells and activated postsynaptic GABAA and GABAC receptors in RB cells. The sensitivity of ACh-induced currents to nicotinic ACh receptor (nAChR) antagonists (TMPH ~ mecamylamine > erysodine > DhβE > MLA) together with the differential potency of specific agonists to mimic ACh responses (cytisine >> RJR2403 ~ choline), suggest that A17 cells express heteromeric nAChRs containing the β4 subunit. Activation of nAChRs induced GABA release after Ca2+ accumulation in A17 cell dendrites and varicosities mediated by L-type voltage-gated calcium channels (VGCCs) and intracellular Ca2+ stores. Inhibition of acetyl-cholinesterase depolarized A17 cells and increased spontaneous inhibitory postsynaptic currents in RB cells, indicating that endogenous ACh enhances GABAergic inhibition of RB cells. Moreover, injection of neostigmine or cytisine reduced the b-wave of the scotopic flash electroretinogram, suggesting that cholinergic modulation of GABA release controls RB cell activity in vivo. These results describe a novel regulatory mechanism of RB cell inhibition and complement our understanding of the neuromodulatory control of retinal signal processing.